Civilization ecological instead of civilization immediate - Najder-Stefaniak, Krystyna (Studia Ecologiae et Bioethicae, 2005)
In the paper has been presentend two possible replies of human being to situation, whites imply contemporary world. One – civilization immediate – consist in adaptation of this situation, second – civilization ecological – consist in creative transcendence of this situation First – enter in modern paradigm of thinking, other – in paradigm of ecological thinking.